2017
DOI: 10.1371/journal.pone.0173522
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of traditional medicine use for malaria alongside free antimalarial drugs treatment amongst adults in high-risk malaria endemic provinces of Indonesia

Abstract: BackgroundThe level of traditional medicine use, particularly Jamu use, in Indonesia is substantial. Indonesians do not always seek timely treatment for malaria and may seek self-medication via traditional medicine. This paper reports findings from the first focused analyses of traditional medicine use for malaria in Indonesia and the first such analyses worldwide to draw upon a large sample of respondents across high-risk malaria endemic areas.MethodsA sub-study of the Indonesia Basic Health Research/Riskesda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Broadly speaking traditional medicine use is common amongst people of all levels of education, community size and place of residence. This level of traditional medicine use is comparable with other studies from the region and elsewhere [11][12][13]. Research by Suswardany in neighbouring Indonesia found that respondents used traditional medicine for general health/common illness purposes every day [13].…”
Section: Discussionsupporting
confidence: 86%
“…Broadly speaking traditional medicine use is common amongst people of all levels of education, community size and place of residence. This level of traditional medicine use is comparable with other studies from the region and elsewhere [11][12][13]. Research by Suswardany in neighbouring Indonesia found that respondents used traditional medicine for general health/common illness purposes every day [13].…”
Section: Discussionsupporting
confidence: 86%
“…Indonesian people consider themselves healthy if they can perform their everyday activities without disruption. Thus, people generally sought help when symptoms hindered these [21,22,25,28,37,39,42,45,51,56,66,67,71,77]. For example, Eeuwijk [71] described that most older people sought care from health professionals for rheumatism because it hindered their activities.…”
Section: Lay Concepts Of Health and Illnessmentioning
confidence: 99%
“…Age, household size, education, and economic status determine people's choices of health providers [65,74,94]. Poorer households were more likely to use traditional medicines for treating malaria [25], older people and those in rural areas were more likely to seek traditional and alternative treatment [84,89,96]. Women were also more likely to seek health care for tuberculosis-related symptoms [21].…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not to say that TCIM may not have a role in infectious disease treatment. Current evidence suggests TCIM is being used to manage and treat malaria, tuberculosis and HIV/AIDSthough importantly these are usually integrated as part of a suite of bestpractice care and are usually focused on chronic, ongoing postinfection symptoms [3][4][5][6]. Alongside growing evidence of use, antiviral activity of TCIM products against dengue [7] and chikungunya [8] has been reported, and preclinical reports or phase one clinical trials suggest some TCIM may be effective in treating these viral infections [9][10][11].…”
Section: Traditional and Complementary Treatments Do Have A Role To Pmentioning
confidence: 99%